Применение энтропийного коэффициента для оптимизации числа интервалов при интервальных оценках - Тыныныка, А.Н. (Технология и конструирование в электронной аппаратуре, 2017)
Показано, что в качестве критерия выбора числа интервалов группирования опытных данных при интервальных оценках может использоваться энтропийный коэффициент. В соответствии с описанной процедурой быстрого определения числа интервалов на массиве данных исследована точность имеющихся в литературе и предложенных новых формул. Проведен анализ в сравнении с ранее опубликованными результатами применения для этих целей критерия согласия Пирсона. Сделаны расчеты с целью сравнения эффективности применения одних и тех же формул при распределении выборочных данных по нормальному закону и по закону Рэлея. Показано, що як критерій вибору числа інтервалів групування досліджених даних при інтервальних оцінках можна використовувати ентропійний коефіцієнт. Відповідно до описаної процедури швидкого визначення числа інтервалів на масиві даних досліджено точність наявних в літературі і запропонованих нових формул. Проведено аналіз в порівнянні з раніше опублікованими результатами застосування для цих цілей критерію згоди Пірсона. Зроблено розрахунки з метою порівняння ефективності застосування одних і тих самих формул при розподілі вибіркових даних за нормальним законом і за законом Релея. In solving many statistical problems, the most precise choice of the distribution law of a random variable is required, the sample of which the authors observe. This choice requires the construction of an interval series. Therefore, the problem arises of assigning an optimal number of intervals, and this study proposes a number of formulas for solving it. Which of these formulas solves the problem more accurately? In [9], this question is investigated using the Pearson criterion. This article describes the procedure and on its basis gives formulas available in literature and proposed new formulas using the entropy coefficient. A comparison is made with the previously published results of applying Pearson's concord criterion for these purposes. Differences in the estimates of the accuracy of the formulas are found. The proposed new formulas for calculating the number of intervals showed the best results. Calculations have been made to compare the work of the same formulas for the distribution of sample data according to the normal law and the Rayleigh law.